2017
DOI: 10.31254/jmr.2017.3208
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Sexually Transmitted Infections knowledge and practices: a survey of female secondary school students in Enugu, South East Nigeria

Abstract: Background:The discovery of HIV has re-awakened global interest in sexually transmitted infections. As a means of curbing the spread, several efforts have been made at educating people so as to positively influence their sexual practices. Aim: The aim of this study was to determine the knowledge and practice of female secondary school students to sexually transmitted infections in Enugu, South East Nigeria. These could not only pose as barriers to effective sexual education and impair case management but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
2
7
1
Order By: Relevance
“…The study was a community-based, descriptive, cross-sectional study. The Cochrane's formula for descriptive study, n = z 2 pq/d 2 , was used, with a standard normal deviation at 95% confidence interval (1.96), a prevalence rate of 62.5% (0.625) from a similar study carried out in Enugu, South East Nigeria, 12 and an error of precision at 5% (0.05). The minimum sample size was 360.…”
Section: Study Population Design Sample Size Determination and Selection Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a community-based, descriptive, cross-sectional study. The Cochrane's formula for descriptive study, n = z 2 pq/d 2 , was used, with a standard normal deviation at 95% confidence interval (1.96), a prevalence rate of 62.5% (0.625) from a similar study carried out in Enugu, South East Nigeria, 12 and an error of precision at 5% (0.05). The minimum sample size was 360.…”
Section: Study Population Design Sample Size Determination and Selection Of Participantsmentioning
confidence: 99%
“…A pretested, interviewer-administered, semi-structured questionnaire adapted from the reviewed literature 12,13,14,15,16 was used for data collection. The questionnaire consisted of four sections: Section A consisted of questions on socio-demographic characteristics of the respondents, while Section B had questions on the knowledge of the respondents about STIs.…”
Section: Study Instrument and Data Collectionmentioning
confidence: 99%
“…In our study, it was determined that, from STDs, hepatitis B and hepatitis C are less known by students, whereas students do not know other STDs such as syphilis, gonorrhea, genital herpes, trichomonas, and chlamydia. In other studies, although HIV/AIDS is the most known disease, it can be seen that other STDs are less known (21)(22)(23)(24)(25). As AIDS disease is frequently shown in media, and a current and important problem, its status of being known is higher compared to other diseases.…”
Section: Discussionmentioning
confidence: 96%
“…In the study of Amu and Adegun, it was determined that best-known disease was AIDS and gonorrhea, respectively (21). In a study conducted with female students by Nwatu et al, it was found that the most known diseases were gonorrhea, AIDS and syphilis, respectively, and the least known disease was genital herpes (22). In our study, it was determined that, from STDs, hepatitis B and hepatitis C are less known by students, whereas students do not know other STDs such as syphilis, gonorrhea, genital herpes, trichomonas, and chlamydia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation